A new numerical scheme for solving system of Volterra integro-diﬀerential equation - Loh, Jian Rong; Phang, Chang (Elsevier, 2017)
In this article, we apply Genocchi polynomials to solve numerically a system of Volterra integro-differential equations. This is done by approximating functions using Genocchi polynomials and derivatives using Genocchi polynomials operational matrix of integer order derivative. Com-bining approximation with collocation method, the problem is reduced to a system of algebraic equations in terms of Genocchi coefﬁcients of the unknown functions. By solving the Genocchi coefﬁcients, we obtain good approximate functions of the exact solutions of the system. A few numerical examples show that our proposed Genocchi polynomials method achieves better accu-racy compared to some other existing methods.